Stream of consciousness in Patrick McCabe’s The Butcher Boy - Abdul, Zanyar Kareem; Noor, Rohimmi; Talif, Rosli (Universiti Putra Malaysia Press, 2013)
Stream of consciousness is a narrative technique that is commonly seen as a product of the modernist era. It is a literary technique characterized by introspection, self-awareness, and openness to the unconscious. Associated primarily with Joyce and Woolf, the technique is a way of representing the whole mind of an individual, not just conscious thoughts. It is based on the psychological theory that human minds are made of many layers of awareness. McCabe is a prominent contemporary Irish writer who has a penchant for the technique and its employment in novels. This article examines the psyche and behaviour of the main character, Francie Brady, in the novel, The Butcher Boy. McCabe uses a crucial tool, the stream of consciousness to let the psyche of a child talk and show readers what the character desires to convey. He is creative in attracting readers’ attention to the mind of his characters. McCabe’s use of the technique may be different from others because there is no separation between the dialogues and the thoughts, albeit with little use of punctuation in addition to shifting from one story to another. Elements that are used in depicting stream of consciousness are narration, use of punctuation, familial and societal issues, obsession, and madness, trauma and conduct disorder.